PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2013-2017) - Dingkol, Mohamad S. E.; Murni, Sri; Tulung, Joy Elly (FEB Universitas Sam Ratulangi Manado, 2020)
The rapid development of the Indonesia Stock Exchange (IDX) currently cannot shift the role of investors conducting transactions on the IDX, through the capital market which is a liaison between investors (those who have funds) and companies (those who need long-term funds). Financial ratio analysis can help business people, governments and financial users for the company's financial needs. Types of financial ratios that are often used in a company's financial valuation are liquidity ratios, activity ratios, solvency ratios, profitability ratios, and market ratios. Profitability, liquidity, solvency, activities and markets do not have a positive influence on the company's stock price. Liquidity, solvency, activities and markets do not have a significant effect on stock prices. Profitability has a significant influence on stock prices. Food and beverage industry subsectors listed on the Indonesia Stock Exchange (IDX) need to increase share prices. Improve and focus company performance on strategies that can be used in managing finances before specifically for liquidity, solvency, activity and market performance.KeywordsÂ :Â Â financial performance, profitability, liquidity, solvency, activities, markets, stock prices